Transparent Electrodes Consisting of a Surface‐Treated Buffer Layer Based on Tungsten Oxide for Semitransparent Perovskite Solar Cells and Four‐Terminal Tandem Applications. Issue 5 (2nd April 2020) - Park, Helen Hejin; Kim, Jincheol; Kim, Geunjin; Jung, Hyunmin; Kim, Songhee; Moon, Chan Su; Lee, Seon Joo; Shin, Seong Sik; Hao, Xiaojing; Yun, Jae Sung; Green, Martin A.; Ho‐Baillie, Anita W. Y.; et al.
Abstract: For semitransparent devices with n‐i‐p structures, a metal oxide buffer material is commonly used to protect the organic hole transporting layer from damage due to sputtering of the transparent conducting oxide. Here, a surface treatment approach is addressed for tungsten oxide‐based transparent electrodes through slight modification of the tungsten oxide surface with niobium oxide. Incorporation of this transparent electrode technique to the protective buffer layer significantly recovers the fill factor from 70.4% to 80.3%, approaching fill factor values of conventional opaque devices, which results in power conversion efficiencies over 18% for the semitransparent perovskite solar cells. Application of this approach to a four‐terminal tandem configuration with a silicon bottom cell is demonstrated. Abstract : A tungsten oxide (WO x ) layer with niobium oxide surface treatment is introduced as a sputter buffer for semitransparent perovskite solar cells. Compared to devices with an untreated WO x buffer, using the surface‐treated buffer significantly recovers the fill factor, which is possibly explained via electronic‐trap shifting toward the band edge. Incorporation of this approach is demonstrated for four‐terminal perovskite‐silicon tandems.